Bivalirudin exerts antiviral activity against respiratory syncytial virus-induced lung infections in neonatal mice - Zhuang Shihao; Tang Qiuyu; Chen Ping; Wang Chengyi; Liu Guanghua (Acta Pharmaceutica)
Respiratory syncytial virus (RSV) is the most common cause of small airways inflammation in the lungs (bronchiolitis) in neonates and immunocompromised adults. The deregulation of cellular and plasma components leads to increased morbidity and mortality. The activation of the clotting cascade plays a key role in the progression of disease severity during viral infection. The current investigation studied the effect of bivalirudin (BR) on the progression and cellular effects of RSV-induced infection in the neonatal mice model. Mice (5–7 days old) were inoculated intranasally with RSV with or without BR administration (2 mg kg−1 day−1, i.v.) for 2 weeks. Tissue histopathology, inflammatory signalling genes such as TLR, and cytokines were analyzed. The results showed pneumocytes exhibiting nuclear pyknosis, cellular infiltration in lung tissue and increased lung titers in RSV-infected mice compared to the control. Furthermore, RSV-infected mice demonstrated altered clotting parameters such as D-dimer, soluble thrombomodulin, and increased inflammatory cytokines IL-5, 6, IFN-γ, IL-13, and CXCL1. Additionally, the mRNA expression analysis displayed increased levels of IL-33, TLR3, and TLR7 genes in RSV-infected lung tissue. Further, to delineate the role of micro RNAs, the qRT-PCR analysis was done, and the results displayed an increase in miR-136, miR-30b, and let-7i. At the same time, the down-regulated expression of miR-221 in RSV-infected mice compared to the control. BR treatment reduced the cellular infiltration with reduced inflammatory cytokines and normalized clotting indices. Thus, the study shows that RSV infection induces specific changes in lung tissue and the clotting related signalling mechanism. Additionally, BR treatment significantly reduces bronchiolitis and prevents the severity of the infections suggesting that BR can possibly be used to reduce the viral-mediated infections in neonates.